Northern Range, Trinidad - (:unkn) unknown (Print Master Limited, Trinidad, 2010)
Photo showing the Northern Range in Trinidad.
Colour: Blue and Green Hues; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; [1980]; Scenic overlooks--Trinidad and Tobago; Northern Range